ANALISIS PERAN BSI KCP GATOT SUBROTO DI KOTA JAMBI DALAM PEMBERDAYAAN UMKM MELALUI PEMBIAYAAN MURABAHAH - Dimas Albani; Efni Anita; Nurfitri Martaliah (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze the role of Bank Syariah Indonesia (BSI) Gatot Subroto Sub-Branch Office in Jambi City in empowering Micro, Small, and Medium Enterprises (MSMEs) through murabahah financing schemes. The background of this research lies in the vital role of the MSME sector as a key driver of the national economy and the contribution of Islamic financial institutions in supporting community-based economic growth. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation involving bank representatives and MSME beneficiaries of murabahah financing. The findings indicate that BSI Gatot Subroto Sub-Branch plays an active role in MSME empowerment by providing accessible murabahah financing, business mentoring, and Islamic financial literacy programs. Murabahah financing has been found to support MSME actors in increasing business capital, expanding business networks, and improving production capacity. However, challenges remain, such as limited Islamic financial literacy among MSME actors and relatively lengthy administrative procedures. The study concludes that murabahah financing significantly contributes to MSME empowerment in Jambi City, provided that financial literacy enhancement and process simplification are carried out to optimize the outcomes.